Environmental Applications of Geochemical Modeling. - Zhu, Chen, 1962-; Anderson, G. M. (Gregor Munro), 1932- (Cambridge University Press, 2002)
Annotation Geochemical modeling is a powerful tool for characterizing environmental site contaminations and predicting environmental impacts. This book discusses the application of geochemical models to environmental practice and studies, through the use of numerous case studies of real-world environmental problems, such as acid mine drainage, pit lake chemistry, nuclear waste disposal, and landfill leachates. In each example the authors clearly define the environmental threat in question; explain how geochemical modeling may help solve the problem posed; and advise the reader how to prepare input files for geochemical modeling codes and interpret the results in terms of meeting regulatory requirements. Support material for the book, including program codes, input files and exercise problems, is available on the Internet. Environmental Applications of Geochemical Modeling will serve as an advanced textbook for courses in environmental geochemistry, and as an indispensable reference for professional hydrogeologists, geochemists, engineers, and regulators, working within the environmental spheres.